(untitled) (Modern education and development, 2025)
This article analyzes the relationship between the concept of the green economy, sustainable development and environmental problems. The green economy is aimed at ensuring economic growth, combining the use of Natural Resources and Environmental Protection. The article examines the importance of the green economy to address environmental issues such as global climate change, pollution, and decreased biodiversity. Also, on the example of Uzbekistan, the implementation of Sustainable Development Strategies and the economic and social benefits of the introduction of green technologies are analyzed. The challenges and opportunities faced during the transition to a green economy are also considered. The article highlights the importance of Economic Policy and public participation in addressing environmental issues and outlines measures to be taken in the future towards sustainable development.